2018
DOI: 10.1002/marc.201800433
|View full text |Cite
|
Sign up to set email alerts
|

TBD‐Catalyzed Ring‐Opening Polymerization of Alkyl‐Substituted Morpholine‐2,5‐Dione Derivatives

Abstract: In a two-step synthesis, five different alkyl-substituted morpholine-2,5-dione monomers were synthesized from the natural amino acids glycine, alanine, valine, leucine, and isoleucine. The heterocyclic compounds crystallize in a boat-like conformation and are polymerized via 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD)-catalyzed ring-opening polymerization (ROP) in tetrahydrofuran. Well-defined polymers could be obtained from the monomers based on valine, leucine, and isoleucine at a feed ratio of M/I/TBD = 100/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 45 publications
5
46
0
Order By: Relevance
“…We suggest these are driven by transesterification type reactions that could potentially limit the production of longer chain PMDs via mechaROP. Furthermore, this underscores the importance of quenching the reaction once the monomer conversion has ceased to evolve, an observation which is analogous to the solution-based ROPs. , …”
mentioning
confidence: 88%
See 1 more Smart Citation
“…We suggest these are driven by transesterification type reactions that could potentially limit the production of longer chain PMDs via mechaROP. Furthermore, this underscores the importance of quenching the reaction once the monomer conversion has ceased to evolve, an observation which is analogous to the solution-based ROPs. , …”
mentioning
confidence: 88%
“…In each case, the molecular weights were low and chain distributions were broad. This lack of control was equally observed for the solution-based ROP of MD wherein detrimental intra- and intermolecular transesterifications occurred. , Furthermore, DBU may deprotonate the amide proton on MD, forming a cyclic imidate which can in turn catalyze the polymerization of other monomers. ,, To overcome these effects, hydrogen bond donors such as 3-[3,5-bis­(trifluoromethyl)­phenyl]-1-cyclohexylthiourea (TU) can be used, granting better control over the polymerization of MD and other monomers. ,, In solution-based systems, 5 equiv of TU were necessary for the controlled synthesis of different PMDs (ranging from 8 to 18 kg mol –1 ) . Hence, as to determine whether TU acts in the same fashion during the mechaROP of MD, two tests were carried out with 2.5 equiv (PMD10) and 5 equiv (PMD11) of TU.…”
mentioning
confidence: 99%
“…Polydepsipeptides (PDPs) contains α-hydroxy acids and α-amino acids groups in the repeating unit of the polymer chain and can be obtained by ROP of morpholine-2,5-dione derivatives (MDs). 183 The ROPs of MDs have been well explored with metal catalysts, enzymes and organocatalysts. Recently, Du and Li reported that using binary catalytic systems of TU with DBU or TBD, the polymerizations were well-controlled, producing the PDPs with controlled molecular weights and low dispersities.…”
Section: Scheme 20mentioning
confidence: 99%
“… Reagents and conditions: (a) DMAP, BOP reagent, CH 2 Cl 2 , 2 or MeSO 3 H, CHCl 3 , Δ; 3 (b) DEAD, THF; 2 (c) Amberlyst 15, toluene, Δ, 2 or p -TsOH, toluene, Δ; 4 , 5 (d) p -TsOH, toluene, Δ, 4 or DBU, MS 4 Å, toluene; 6 (e) NaHCO 3 , DMF, Δ, 7 , 8 or TEA, DMF, Δ, 2 , 9 or DIPEA, CHCl 3 , Δ, 10 or (1) NaOH, EtOH, H 2 O, (2) H 2 SO 4 ; 2 (f) DIPEA, DMSO, 11 or (1) K 2 CO 3 , H 2 O, (2) HCl, 12 or (1) NaOH, EtOH, H 2 O, (2) HCl. 2 …”
Section: Solution-phase Synthesesmentioning
confidence: 99%
“… 23 1,5,7-Triazabicyclo[4.4.0]dec-5-ene (TBD) was a particularly active catalyst for the generation of polymers 38 (R 1 = H, R 2 = H or alkyl) from corresponding DKMs 1 using benzyl alcohol as an initiator. 7 Several bases, such as 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), were investigated in polymerizations of methionine-derived DKMs 1 (R 1 = H or alkyl, R 2 = CH 2 CH 2 SCH 3 ). 8 The resulting poly(ester amides) 38 were applicable for postpolymerization modifications via “methionine click” chemistry.…”
Section: Chemical Reactivity and Utilization In Ring-opening Polymerizationsmentioning
confidence: 99%